2021
DOI: 10.1038/s41598-021-84422-3
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen addition decreases methane uptake caused by methanotroph and methanogen imbalances in a Moso bamboo forest

Abstract: Forest soils play an important role in controlling global warming by reducing atmospheric methane (CH4) concentrations. However, little attention has been paid to how nitrogen (N) deposition may alter microorganism communities that are related to the CH4 cycle or CH4 oxidation in subtropical forest soils. We investigated the effects of N addition (0, 30, 60, or 90 kg N ha−1 yr−1) on soil CH4 flux and methanotroph and methanogen abundance, diversity, and community structure in a Moso bamboo (Phyllostachys eduli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 96 publications
0
8
0
Order By: Relevance
“…Thus, a higher abundance of mcrA genes can be expected in topsoils. As for methanogens, which are strictly anaerobic organisms, the presence of mcrA genes has previously been shown in oxic soils in anaerobic microniches (Frey et al, 2011;Li et al, 2021). In addition, anaerobic methanotrophs have been reported that can oxidize methane produced by methanogens (Luesken et al, 2012).…”
Section: Differentially Abundant Genes Of C and N-transforming Processesmentioning
confidence: 93%
“…Thus, a higher abundance of mcrA genes can be expected in topsoils. As for methanogens, which are strictly anaerobic organisms, the presence of mcrA genes has previously been shown in oxic soils in anaerobic microniches (Frey et al, 2011;Li et al, 2021). In addition, anaerobic methanotrophs have been reported that can oxidize methane produced by methanogens (Luesken et al, 2012).…”
Section: Differentially Abundant Genes Of C and N-transforming Processesmentioning
confidence: 93%
“…The "three stages" concept is primarily determined by the biphasic dose-response relationship between N input and biotic processes, exhibiting a stimulating effect at low doses and a suppressing effect at high doses (referred to as the "hormesis" effect; (Agathokleous et al, 2020). Additionally, the asynchronous responses of methane production and oxidation processes to N input play a role; the hormesis effect leads to the transition from Stage I to subsequent stages, and the transition from Stage II to Stage III occurs due to the lower tolerance of methanotrophs to N input as compared to methanogens (Li et al, 2021). While methanotrophs are generally sensitive to nitrogen addition (Nyerges & Stein, 2009), at least some methanogens (such as hydrogenotrophic methanogens) are tolerant to high N and low soil pH (Horn Marcus et al, 2003).…”
Section: Global Forest Soil Ch 4 Fluxes and The Underlying Environmen...mentioning
confidence: 99%
“…Nitrogen addition was found to decrease methane uptake in a natural environment containing methanotrophs and methanogens [100]. For the effect of ammonia on methanotrophs growth, see [101].…”
Section: Bacillus Firmus (Ncimb Strain 13280)mentioning
confidence: 99%